20 ETROLIZUMAB IMPROVED ENDOSCOPIC SCORE, PATIENT-REPORTED OUTCOMES, AND INFLAMMATORY BIOMARKERS IN PATIENTS WITH MODERATE TO SEVERE UC WHO HAD FAILED TNF ANTAGONIST THERAPY: THE HICKORY OPEN-LABEL INDUCTION (OLI) COHORT. (18th January 2018) - Peyrin-Biroulet, Laurent; Rubin, David T; Feagan, Brian; Oh, Young S; Arulmani, Udayasankar; Tyrrell, Helen; Maciuca, Romeo; Williams, Sarah; Tole, Swati; Thommes, James
Abstract: Background: Patients with ulcerative colitis (UC) who have experienced failure of TNF antagonist (aTNF) therapy are a difficult-to-treat population with a notable unmet medical need. Centrally read endoscopy demonstrates reduced placebo remission rates as low as 0%–8% in this population (1, 2). HICKORY OLI evaluates etrolizumab in patients intolerant/refractory to aTNFs. Methods: Patients received etrolizumab 105 mg every 4 weeks in a 14-week induction period. Endoscopic subscore (ES) and patient-reported rectal bleeding (RB) and stool frequency (SF) were assessed at baseline (BL) and week 14. Assessed outcomes were clinical response: ≥ 3-point and 30% reduction of Mayo Clinic score (MCS) from BL and ≥ 1-point decrease in RB or RB ≤ 1; remission: MCS ≤ 2, with individual subscores ≤ 1 and RB = 0; endoscopic improvement: ES ≤ 1; RB remission: RB = 0; SF remission: SF ≤ 1 with ≥ 1-point reduction from BL. Results: HICKORY OLI enrolled 130 patients with aTNF failure; 45% with failure of > 1 aTNF. BL scores were mean MCS of 9.4 and median fecal calprotectin (FC) of 1778 mg/kg. At week 14, SF remission was achieved in 35.4% of patients, RB remission in 52.3%, clinical response in 50.8%, remission in 12.3%, and ES ≤ 1 in 23.9%. In the 43.9% of patients with ≥ 1-point improvement in ES, there was an association with higher rates of SF and RB remission. Among those with ES = 0, 90% reported SF ≤ 1, and 100% reported RB ≤ 1 (Fig 1). Patients achieving SF remission, RB remission, or ES ≤ 1 demonstrated > 70% geometric mean reduction in FC. Conclusions: In aTNF-failed patients with high disease burden, etrolizumab achieved clinically meaningful response, remission, and endoscopic improvement. Patients who had improved ES achieved higher rates of RB and SF remission and greater reductions in inflammatory biomarkers. Recruitment is ongoing. 1. Vermeire S, et al. Lancet. 2014;384:309–318. 2. Sandborn W, et al. N Engl J Med. 2017;376:1723–1736.